Vegetarianism during pregnancy: Risks and benefits - Costa-Rodrigues, Joao (2020)
Background During pregnancy, women face continuous nutritional challenges. Although it is a personal choice, the adoption of a vegetarian dietary pattern during pregnancy must be regarded as a situation that may be associated with some risks and benefits for the mother and the fetus. Scope and Approach In the present review, the most frequent nutritional deficits among pregnant vegetarians will be discussed, namely, those that refer to vitamin B12, zinc, iron, omega-3 fatty acids and vitamin D. If properly planned, vegetarian diets may also be associated with some important health benefits. The main potential outcomes of vegetarianism for pregnant women, fetal development and for the early and later life of the newborns will be also reviewed. Key Findings and Conclusions Taken together, despite some of the controversial published data, vegetarianism appears to be a safe dietary pattern during that period of time. So, the option for vegetarianism must be considered a personal choice that like any other feeding pattern may pose some nutritional risks but also bring some potential health outcomes both for the mother and for the children. In order to deal with the nutritional requirements during pregnancy, it is recommended that vegetarian mothers follow strict nutritional counseling.